Virus Disinfection from Environmental Water Sources Using Living Engineered Biofilm Materials. Issue 14 (22nd May 2020) - Pu, Jiahua; Liu, Yi; Zhang, Jicong; An, Bolin; Li, Yingfeng; Wang, Xinyu; Din, Kang; Qin, Chong; Li, Ke; Cui, Mengkui; Liu, Suying; Huang, Yuanyuan; et al.
Abstract: Waterborne viruses frequently cause disease outbreaks and existing strategies to remove such viral pathogens often involve harsh or energy‐consuming water treatment processes. Here, a simple, efficient, and environmentally friendly approach is reported to achieve highly selective disinfection of specific viruses with living engineered biofilm materials. As a proof‐of‐concept, Escherichia coli biofilm matrix protein CsgA was initially genetically fused with the influenza‐virus‐binding peptide (C5). The resultant engineered living biofilms could correspondingly capture virus particles directly from aqueous solutions, disinfecting samples to a level below the limit‐of‐detection for a qPCR‐based detection assay. By exploiting the surface‐adherence properties of biofilms, it is further shown that polypropylene filler materials colonized by the CsgA‐C5 biofilms can be utilized to disinfect river water samples with influenza titers as high as 1 × 10 7 PFU L −1 . Additionally, a suicide gene circuit is designed and applied in the engineered strain that strictly limits the growth of bacterial, therefore providing a viable route to reduce potential risks confronted with the use of genetically modified organisms. The study thus illustrates that engineered biofilms can be harvested for the disinfection of pathogens from environmental water samples in a controlled manner and highlights the unique biology‐only properties of living substances for material applications. Abstract : A simple, efficient, and environmentally friendly approach to achieve highly selective disinfection of specific viruses with living engineered biofilm materials from virus‐polluted water is reported. The engineered biofilms can disinfect influenza virus from contaminated water to a level below the limit‐of‐detection for a qPCR‐based detection assay, thus protecting mammalian cells against virus infections efficiently.